2000
DOI: 10.1116/1.1321283
|View full text |Cite
|
Sign up to set email alerts
|

Nanoheteroepitaxy: Nanofabrication route to improved epitaxial growth

Abstract: Nanoheteroepitaxy is a fundamentally new epitaxial approach that utilizes three-dimensional stress relief mechanisms available to nanoscale heterostructures to eliminate defects provided the island diameter is below a critical value 2lc. Analysis shows that 2lc∼(15–30)× the critical thickness hc. In the case of GaAs on Si (∼4% misfit), 2lc∼40 nm. In material systems such as GaN on Si (∼20% misfit), where the misfit is much larger and interfacial defects are unavoidable, the nanoheteroepitaxial structure is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 20 publications
0
43
0
1
Order By: Relevance
“…Four stages of the growth process were identified as (1) growth initiation, (2) lateral growth, (3) coalescence, and (4) planarization. This study emphasizes stages (1), (2) and, in particular, addresses the effect that growth initiation has on the quality of GaAs during lateral growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four stages of the growth process were identified as (1) growth initiation, (2) lateral growth, (3) coalescence, and (4) planarization. This study emphasizes stages (1), (2) and, in particular, addresses the effect that growth initiation has on the quality of GaAs during lateral growth.…”
Section: Methodsmentioning
confidence: 99%
“…9 For example, nanoheteroepitaxy theory predicts that growth of GaAs on Si (~4% misfit) should support a coherent interface provided the island size is below the critical island diameter (2l c ) of 40 nm. 2 Nanoheteroepitaxy addresses highly lattice mismatched and polarity mismatched systems that are expected to grow in Stranski-Krastanov or VolmerWeber mode. One example is the growth of GaAs on Si which becomes three-dimensional (3D) at an early stage of film growth (<7 nm) to minimize the strain Initial Nanoheteroepitaxial Growth of GaAs on Si(100) by OMVPE D. ZUBIA, 1,2,4 S. ZHANG, 1,2 R. BOMMENA, 1,2 X.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the glide plane is suitably oriented, the dislocations formed on the terrace of c-NPSS can glide and climb to a terrace edge. Finally, the epitaxial lateral overgrowth was performed the continuous epitaxial film [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The FWHM of the GaN rocking curves was 0.0852° and 0.2181° for the (10.5) and (00.2) reflection peak, respectively. Following Zubia et al [9], the higher the mismatch of the material system, to which NHE is applied, the smaller the critical diameter of the nano-islands. We observed that the overgrowth of a nanocrystalline AlN film only succeeded, if the diameter of the crystallites as deposited was small as 20-30 nm.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by Zubia et al [7], in case of NHE, the strain decays exponentially with distance to the interface in both materials, resulting in an unstrained epilayer at a thickness of only 100 nm. NHE as well as the method of epitaxial lateral overgrowth at the nanoscale (nano-ELOG) [8] are commonly applied to prepatterned substrates, where the islands and masked areas are defined by lithographical means prior to the growth [9]. However, Luryi and Suhir [10] predicted a favourable island size of about 10-100 nm, which requires interferometric optical lithography or the extensive technology of electron beam lithography.…”
mentioning
confidence: 99%